A novel braided biodegradable stent for use in congenital heart disease: Short‐term results in porcine iliac artery. Issue 8 (12th April 2019) - Sun, Jing; Sun, Kun; Bai, Kai; Chen, Sun; Wang, Fujun; Zhao, Fan; Hong, Nanchao; Hu, Hanbo
Abstract: To evaluate the properties and efficacy of a novel braided biodegradable stent (BBS) consisting of poly (p‐dioxanone) (PPDO) and polycaprolactone (PCL) for usage in children with congenital cardiovascular diseases. PCL/PPDO composite filaments were fabricated by coating PCL layers onto PPDO filaments, which were fused with PPDO monofilaments to form the BBS. Physical properties of BBSs including elastic recovery rate, deformation rate, and mechanical characteristics with adjunctive post‐dilation were evaluated by radial force‐tests. Ten BBS stents and 10 metallic wall stents (WS) as controls were implanted into the common carotid arteries of 10 pigs and angiography as well as histological examinations were performed 4 and 8 weeks after implantation. An 8 mm BBS with adjunctive post‐dilation had the best morphological retention and dimension stability being similar to an 8 mm WS. Luminal gain percentages of BBS and WS immediately, 4 weeks and 8 weeks after implantation were 20.44 ± 2.82% and 27.08 ± 0.88%, 12.34 ± 0.18% and 17.32 ± 8.24%, as well as −1.76 ± 2.45% and − 0.98 ± 3.23%. Luminal areas, internal elastic laminas, neointimal areas, neointimal thicknesses, and area stenosis were not significantly different at 4 weeks and 8 weeks after implantation. Injury and inflammation were similar in both groups and no malposition, thrombosis or dissection occurred. BBS with adjunctive post‐dilation showed good physical properties and mechanical stability noninferior to WS. In vivo evaluations showed that a BBS with post‐ballooning had similar short‐term outcomes as a WS. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 1667–1677, 2019.